2012
DOI: 10.1186/1471-2202-13-142
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of gait and neurochemical correlation in a classical murine model of Parkinson’s disease

Abstract: BackgroundGait deficits are important clinical symptoms of Parkinson’s disease (PD). However, existing behavioral tests for the detection of motor impairments in rodents with systemic dopamine depletion only measure akinesia and dyskinesia, and data focusing on gait are scarce. We evaluated gait changes in the methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced C57BL/6 murine model of PD by using a computer-assisted CatWalk system. Correlations of gait parameters with tyrosine hydroxylase (TH) protein le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 69 publications
7
41
0
Order By: Relevance
“…Walking speed variation was markedly increased in Ndufs4 −/− mice, indicating hampered and uncoordinated gait. Similar gait abnormalities were found in MPTP-treated C57BL/6 mice, a model for Parkinson's disease [21]. Furthermore, marked differences were found between Ndusf4 −/− and control mice for other dynamic parameters like step cycle, swing speed, body speed and body speed variation.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Walking speed variation was markedly increased in Ndufs4 −/− mice, indicating hampered and uncoordinated gait. Similar gait abnormalities were found in MPTP-treated C57BL/6 mice, a model for Parkinson's disease [21]. Furthermore, marked differences were found between Ndusf4 −/− and control mice for other dynamic parameters like step cycle, swing speed, body speed and body speed variation.…”
Section: Discussionsupporting
confidence: 69%
“…Behavioral testing was performed at three different time points (21,35 and 42 days of age). Here we show, similar as described in the literature [27], impaired rotarod performance in Ndufs4 −/− mice, which was significantly different from control mice at 35 and 42 days of age (F2,43 = 35.35, p < .0001) (Fig.…”
Section: Behavioral Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Test indicators that are limited to monitor either static or dynamic state cannot adequately display both readouts simultaneously [8], and so on. Therefore, although great efforts have been made to measure the gait deficits in these 6-OHDA PD models [5,9,10], the validation and characterization of gait variability is still lacking [11]. In this report we validated gait variability in three different rat PD models of http://dx.doi.org/10.1016/j.neulet.2014.…”
Section: Introductionmentioning
confidence: 90%
“…Studies using analysis of gait in TBI patients have revealed deficits compared to healthy controls. The CatWalk-XT gait-analysis system has been used to measure deficits in a variety of rodent brain-injury models [65][66][67][68]. Gait analysis one month after injury revealed significant (p<0.05) deficits in the TBI group, in locomotor speed and in the swing speed of all four limbs.…”
Section: Locomotor Outcomes 1 Month After Injurymentioning
confidence: 99%